2003
DOI: 10.1084/jem.20021363
|View full text |Cite
|
Sign up to set email alerts
|

Arf6 and Phosphoinositol-4-Phosphate-5-Kinase Activities Permit Bypass of the Rac1 Requirement for β1 Integrin–mediated Bacterial Uptake

Abstract: Efficient entry of the bacterium Yersinia pseudotuberculosis into mammalian cells requires the binding of the bacterial invasin protein to β1 integrin receptors and the activation of the small GTPase Rac1. We report here that this Rac1-dependent pathway involves recruitment of phosphoinositol-4-phosphate-5-kinase (PIP5K) to form phosphoinositol-4,5-bisphosphate (PIP2) at the phagocytic cup. Reducing the concentration of PIP2 in the target cell by using a membrane-targeted PIP2-specific phosphatase lowered bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 52 publications
4
78
1
1
Order By: Relevance
“…Although PIP5K does relocalize to different subcellular domains following stimulation of the platelet thrombin receptor, our data indicate that platelet PIP5K does not traffic into lipid rafts. (19,26,40). We have previously shown that these GTPases regulate the intracellular localization and catalytic activity of PIP5K␣ in Cos7SH cells (33).…”
Section: Time Course Of Pip5k Redistribution In Human Platelets-mentioning
confidence: 99%
“…Although PIP5K does relocalize to different subcellular domains following stimulation of the platelet thrombin receptor, our data indicate that platelet PIP5K does not traffic into lipid rafts. (19,26,40). We have previously shown that these GTPases regulate the intracellular localization and catalytic activity of PIP5K␣ in Cos7SH cells (33).…”
Section: Time Course Of Pip5k Redistribution In Human Platelets-mentioning
confidence: 99%
“…It is involved in cell migration through membrane ruffle formation and podosome formation (16,17,19). Arf6 also affects uptake of pathogens via endocytosis and recycling of ␤1 integrins (20), membrane delivery during phagocytosis, actin remodeling (21,22), intracellular transport of MHCI molecules (21), and the control of Fc␥ receptor-mediated phagocytosis (23,24). Recently, Arf6 was shown to be essential for two receptors that are related to TLR4.…”
mentioning
confidence: 99%
“…Data from other cell types suggest that PIP5Kb is targeted to the plasma membrane and/or activated when overexpressed (24)(25)(26). Overexpression of PIP5Kb induces actin polymerization (27)(28)(29)(30) and actin comets from lipid rafts at the plasma membrane (31).…”
Section: P Hosphatidylinositol 45-biphosphate (Pip2) Represents 1%mentioning
confidence: 99%